Body size and age estimation of Chinese sea bass (Lateolabrax maculatus) and evidence of Late Neolithic fishing strategies, a case study from the Guye site - Yu, Chong; Cui, Yong (Frontiers in Ecology and Evolution, 2022)
Fishing was an important form of subsistence economy among ancient societies. However, details of past fishing activities have been rarely studied in China. This paper uses data extracted from a modern fish collection to estimate the body size and age of Chinese sea bass from the Guye site, a common species that is frequently discovered in archaeological sites of coastal South China. The distribution of body size and age were reconstructed and combined with fish biology and ecology; the current dataset revealed that the main fishing grounds of the Late Neolithic Guye people were close to the shoreline, and the main fishing season was from spring to early autumn.